Landscape dynamics and human impact on high-mountain woodlands in the western Spanish Central System during the last three millennia. (October 2016) - López-Sáez, José Antonio; Abel-Schaad, Daniel; Robles-López, Sandra; Pérez-Díaz, Sebastián; Alba-Sánchez, Francisca; Nieto-Lugilde, Diego
Abstract: A multi-proxy palaeoenvironmental study (pollen, non-pollen palynomorphs, charcoal particles) of a mire, located in the western Spanish Central System (Gredos range), was undertaken to trace historic human activities related to woodland clearance and past land-uses at high altitudes during the last three millennia. The results of this study constrained by 4 AMS radiocarbon measurements are combined with archaeological data and compared with similar research carried out at the same altitude in mountains of central Iberia. The pollen data indicate that high-mountain areas were dominated by birch and pine woodlands until c. 2350 years. From this date on a strong forest decline is recorded during the Late Iron Age and a deeper one c. 1500 years ago in the Visigothic period, which may be related to increasing grazing activities and/or the occurrence of anthropogenic fires. Cereals and faba beans were cultivated in the surrounding valley since c. 2900 cal BP, while chestnut, walnut and olive tree are documented mainly from the Roman period onwards. Highlights: Wild and rugged landscapes require micro-regional paleoecological studies. Grazing activities and anthropogenic fires were the main drivers of vegetation history. Highland spaces of the Gredos range were selectively used during the last three millennia.